Comic Epitaphs: Lucian, Scudéry, and Boileau. (1st July 2013) - Harrison, David
<x xml:space="preserve">Abstract</x> This article seeks to redefine the relationship between Boileau's Dialogue des héros de roman and Madeleine de Scudéry's Clélie. While Boileau wishes to use his text to erase Scudéry from memory, a close reading of the Dialogue and its Lucianic model reveals Scudéry's influence on Boileau's wit. Indeed, the character of Amilcar from Clélie embodies the spirit of Lucianic satire that Boileau hopes to use against Scudéry. Ultimately, Boileau is indebted to a form of enjouement that is inscribed within and popularized by Clélie, and it is this debt that Boileau tries unsuccessfully to make his reader forget in his Dialogue.